Improving Accounting Competencies Based on SAK ETAP for Inkopad Cooperative Employees through Training - Dewi, R. Rosiyana; Arif, Abubakar; Dewi, Risa Nurmala; Aprilia, Hanny; Putri, Amelia Lestari (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: The purpose of this community service program (PKM) is to enhance the accounting competency of employees at the Inkopad cooperative. This is achieved by addressing the gap in their understanding and application of financial accounting standards, specifically the Entity Without Public Accountability (ETAP). Method: This PKM activity employs a training approach to improve the accounting competency of Inkopad cooperative employees. The training spans over three days and utilizes counseling and case resolution methods to provide a comprehensive understanding of ETAP-based accounting. Practical Applications: This PKM serves a dual purpose. Firstly, it assists cooperative employees in preparing financial reports in accordance with ETAP financial accounting standards. This enables stakeholders to make strategic decisions based on accurate financial information. Secondly, it serves as a practical application of Tridharma PT, an academic activity that allows lecturers and students to apply and share their theoretical knowledge with the community. The outcomes of this PKM will also be utilized in campus learning, thereby bridging the gap between theory and practice. Conclusion: The results of this PKM indicate that through the three-day training using counseling and case resolution methods, participants were able to significantly improve their accounting competency based on SAK ETAP. This suggests that such training programs can be effective tools for enhancing accounting competency in cooperative employees.